Cash Transfers, Mental Health and Agency: Evidence from an RCT in Germany - Sandra Bohmann; Susann Fiedler; Maximilian Kasy; Jürgen Schupp; Frederik Schwerter (CESifo GmbH, 2025)
Mental health and wellbeing are unequally distributed in high-income countries, disadvantaging low-income individuals. Unconditional, regular, and guaranteed cash transfers may help address this inequality by promoting financial security and agency. We conducted a preregistered RCT in Germany, where treated participants received monthly payments of EUR 1,200 for three years. Cash transfers improve mental health and wellbeing. These effects are substantively large and robust. Cash transfers also improve perceived autonomy, savings, prosocial giving, time with friends, and sleep. Our findings suggest that cash transfers improve mental health and wellbeing if they empower agency and meaningful life changes.
Keywords: C93; I31; D10; 330; cash transfers; mental health; life satisfaction; purpose in life; agency; autonomy; life changes